17 UMP Graduates are ECRL Trainees - Siti Sarah, Mohamad Rajimi (2017)
Kuantan, 19 November – 17 Universiti Malaysia Pahang (UMP) graduating recently are a part of the trainees for the ECRL Industrial Skills Training Programme (PLKI-ECRL) currently undergoing their training at UMP Gambang Campus. The programme is a collaboration between UMP, Malaysia Rail Link Company (MRL) and China Communications Construction Company (ECRL) Sdn. Bhd. (CCCC) aimed at producing more skilled labour force in the rail industry.